2022
DOI: 10.1186/s12957-022-02572-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pyroptosis-related lncRNA risk model for predicting prognosis and immune response in colon adenocarcinoma

Abstract: Background Colon adenocarcinoma (COAD) is one of the most common malignant tumors and is diagnosed at an advanced stage with a poor prognosis worldwide. Pyroptosis is involved in the initiation and progression of tumors. This research focused on constructing a pyroptosis-related ceRNA network to generate a reliable risk model for risk prediction and immune infiltration analysis of COAD. Methods Transcriptome data, miRNA-sequencing data, and clinica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Moreover, the TME related signatures analysis revealed that CD8 T cell effector and immune checkpoint associated pathway genes were higher in the low‐risk group than in the high‐risk group (Figure 5C). Previous studies revealed that colon adenocarcinoma patients with a higher immune score and more infiltration of antitumor immune cells have a better survival outcome 17–19 . Therefore, we speculated that the better prognosis of the low‐risk group might be related to the more favorable antitumor immune microenvironment.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the TME related signatures analysis revealed that CD8 T cell effector and immune checkpoint associated pathway genes were higher in the low‐risk group than in the high‐risk group (Figure 5C). Previous studies revealed that colon adenocarcinoma patients with a higher immune score and more infiltration of antitumor immune cells have a better survival outcome 17–19 . Therefore, we speculated that the better prognosis of the low‐risk group might be related to the more favorable antitumor immune microenvironment.…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies revealed that colon adenocarcinoma patients with a higher immune score and more infiltration of antitumor immune cells have a better survival outcome. 17 , 18 , 19 Therefore, we speculated that the better prognosis of the low‐risk group might be related to the more favorable antitumor immune microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…In our current work, we found that there was a clear link between the hypoxia score and the amount of COPZ1 in several cancers. Previous studies revealed that a higher immune score was correlated with better survival outcomes [ 45 , 46 ]. We further discovered that the infiltration of antitumor immune cells was higher in the patients with low COPZ1 expression, such as B cells, Neutrophil, CD8+T cells, CD4+T cells and M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have proposed prognostic models for COAD [22][23][24]. However, the studies' predictive performances have not been validated in COAD, and the differences in immune infiltrating cells and immune checkpoint blockade-, immune checkpoint-, and m6A-related genes between the high and low risks of the prediction model were not analyzed.…”
Section: Discussionmentioning
confidence: 99%